Checklist of the genera of Hymenoptera (Insecta) from Espírito Santo state, Brazil - Azevedo, Celso O. (2015)
The first checklist of genera of Hymenoptera from Espírito Santo state, Brazil is presented. A total of 973 genera of Hymenoptera is listed, of which 555 (57%) are recorded for the first time from this state. Ichneumonoidea and Chalcidoidea are the two superfamilies with the most genera, 241 and 203 respectively. Braconidae, with 141 genera, are the richest family.